2010
DOI: 10.1530/eje-09-0958
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic abnormalities in endocrine and metabolic disorders

Abstract: The hemostatic balance is a complex system where the delicate equilibrium is regulated by several factors, including hormones. This review summarizes current knowledge of the effects of most frequent endocrine and metabolic diseases (such as hypothyroidism, hyperthyroidism, Cushing's syndrome, GH-related pituitary dysfunctions, pituitary prolactin-producing adenomas, polycystic ovary syndrome, primary hyperparathyroidism, and metabolic syndrome) on coagulation and fibrinolysis. Overt hypothyroidism appears to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 149 publications
(178 reference statements)
3
64
0
Order By: Relevance
“…Differentiated thyroid cancer patients (nZ112), severely hypothyroid 4-5 weeks following total thyroidectomy without LT 4 replacement, were admitted for RAI thyroid remnant ablation. Before discharge, thyroid hormone suppression therapy (LT 4 , 150 mg/day) was initiated and 6-8 weeks later they were examined in the outpatient follow-up clinic.…”
Section: Patients and Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Differentiated thyroid cancer patients (nZ112), severely hypothyroid 4-5 weeks following total thyroidectomy without LT 4 replacement, were admitted for RAI thyroid remnant ablation. Before discharge, thyroid hormone suppression therapy (LT 4 , 150 mg/day) was initiated and 6-8 weeks later they were examined in the outpatient follow-up clinic.…”
Section: Patients and Study Designmentioning
confidence: 99%
“…However, reports on the influence of thyroid hormones on coagulation and fibrinolysis, while mostly suggesting a hypercoagulable state in thyrotoxicosis, have often been of low methodological quality (3,4,5). Indeed, no high-quality study was identified in a systematic review in 2007 (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because prolonged APTT and PT results indicate a reduced coagulation response and a bleeding tendency, these findings indicate that hyperthyroidism might be associated with hypercoagulability [12] . Previous studies largely have explored patients with clinically overt hypo-or hyperthyroidism who appeared to have an increased risk of bleeding or thrombosis [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Several biological mechanisms have been proposed to explain this intriguing association, including the effects of thyroid hormones on the synthesis of coagulation factors and the thyroid-related autoimmune processes [13,19] . However, the exact mechanism underlying the relationship between FT3 and INR remains unclear.…”
Section: Discussionmentioning
confidence: 99%